Food Guard - Dima Shanti; Masa Anani (My University, 2025)
The world today faces a growing problem of food waste, which negatively impacts food security, the environment, and the economy. This project presents a practical digital initiative aimed at reducing household food waste through the development of an intelligent application called Food Guard. The application enables users to track food products and their expiry dates, receive smart notifications when items are about to expire, and analyze consumption behavior over time—helping them make more conscious decisions about food usage and storage. The system is built using modern technologies, including Flutter for mobile application development, Django with a PostgreSQL database for a secure and robust backend, and Firebase for enabling real-time notifications. Additionally, artificial intelligence is integrated to provide smart storage tips and suggest recipes based on available in- gredients. The application also offers a comprehensive system for managing food donations, whether surplus items or ready-made meals. Food Guard is expected to make a tangible impact on raising food awareness and reducing waste, based on the comprehensive technical solutions it provides and the user-friendly experience it offers. The platform also holds promising potential for fu- ture expansion to support communities and connect them through smart cooperation networks.